Heat shock proteins in osteoarthritis: molecular mechanisms, pathogenic roles, and therapeutic opportunities - Zhao, Bin; Deng, Zhijun; Yang, Zhijun; Yang, Fengyun; Yang, Wenlong (Frontiers in Immunology, 2025)
Osteoarthritis (OA) is the most prevalent degenerative joint disease, characterized by cartilage degradation, chondrocyte apoptosis, synovial inflammation, and subchondral bone remodeling. Accumulating evidence highlights the central role of heat shock proteins (HSPs) in OA pathogenesis and progression. HSPs function as molecular chaperones that maintain proteostasis by facilitating protein folding, preventing aggregation, and modulating stress responses. Dysregulated expression of HSP27, HSP40, HSP60, HSP70, HSP90, and GRP78 contributes to inflammation, extracellular matrix breakdown, and chondrocyte apoptosis, but also provides cytoprotective effects under certain conditions. This duality positions HSPs as both biomarkers of disease activity and promising therapeutic targets. Here, we comprehensively review the roles of HSPs in regulating apoptosis, autophagy, and inflammatory signaling in OA. We further discuss emerging therapeutic strategies that modulate HSP expression or activity, including synthetic drugs, natural products, nanomedicine, stem cell therapy, physical modalities (heat, ultrasound, phototherapy, microwaves), and biological agents such as monoclonal antibodies. By integrating mechanistic insights and translational advances, this review underscores the potential of HSP-targeted therapies to preserve chondrocyte function, maintain extracellular matrix integrity, and slow OA progression, paving the way for novel disease-modifying interventions.